Gender Equity in Commonwealth Higher Education: - Kwesiga, Joy Constance (Kabale University, 2018)
This paper is based on interim findings from a research project on gender equity in higher education in Uganda, Tanzania, South Africa, Sri Lanka and Nigeria. The project, funded by the UK Department for International Development (DFID) and the Carnegie Corporation of New York, and co-ordinated by the Centre for Higher Education Studies at the University of London Institute of Education, is investigating interventions for change in relation to access, curriculum transformation and staff development. It is also searching and analysing published and unpublished literature from low-income Commonwealth countries on gender equity. Themes are emerging in the research. These include the international policy drivers for gender equity, representation of women in senior academic and management posts; access as a redistributive measure, gender violence, organisational culture, micropolitics and the gendered division of labour in academia. There are concerns about the current distribution patterns of women in universities as students, academics and managers and the qualitative experiences of women in Commonwealth universities. The research project offers the opportunity to gain comparative insights across the Commonwealth. It aims to contribute to multilateral